2015
DOI: 10.5301/tj.5000324
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Cardiac Metastasis from Squamous Cell Esophageal Cancer

Abstract: Although heart metastases are uncommon and generally a sign of disseminated disease, they are up to 40 times more frequent than primary cancers of the heart, and typically arise from melanoma or primary mediastinal cancer, but also from lymphoma, breast cancer, esophageal cancer, and leukemia. They are usually asymptomatic and found only at autopsy. Symptomatic patients generally die within a few weeks of diagnosis and usual treatments are chemotherapy, radiotherapy, or both. Surgical resection is recommended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…In total, 164 cases (out of 147 articles) [6153] of unexpected ECM were selected to establish our database. The following data elements were extracted from each article: author name, publication year, article type, patient sex, age at diagnosis, histological type of cancer, tumor location in the esophagus, stage at diagnosis, management of primary tumor, site of metastases, metastasis features (solitary, multiple, synchronous, metachronous, and onset after initial tumor diagnosis), management of metastases, outcomes, and survival.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 164 cases (out of 147 articles) [6153] of unexpected ECM were selected to establish our database. The following data elements were extracted from each article: author name, publication year, article type, patient sex, age at diagnosis, histological type of cancer, tumor location in the esophagus, stage at diagnosis, management of primary tumor, site of metastases, metastasis features (solitary, multiple, synchronous, metachronous, and onset after initial tumor diagnosis), management of metastases, outcomes, and survival.…”
Section: Methodsmentioning
confidence: 99%
“…In all, 12 cases were solitary cardiac metastases. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Most of the cardiac metastasis are detected on autopsy studies. These studies reported the incidence of cardiac metastasis was 2.3%-18.3% of cancer patients and 0.2%-6.5% of unselected autopsy series.…”
Section: Discussionmentioning
confidence: 99%
“…According to the past 15 reports of cardiac metastasis from esophageal cancer, the median time from the detection of primary tumor to the onset of cardiac metastasis was 8.9 months. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] The differential diagnosis of cardiac mass is difficult. In case of a cardiac tumor, metastasis is more frequent than a primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] What is more, cardiac metastatic tumors are often asymptomatic that they are found only at autopsy and seldom be reported. [ 2 ] Mainly malignant melanoma and primary mediastinal tumors, but also lymphoma, lung carcinoma, breast, esophagus, and leukemia, are cause of cardiac metastases. [ 3 ] In case of cardiac metastatic tumors, the prognosis is poor and therapeutic options limited.…”
Section: Introductionmentioning
confidence: 99%